Atomic force microscopy as a tool for assessing the cellular elasticity and adhesiveness to identify cancer cells and tissues. (January 2018) - Zemła, Joanna; Danilkiewicz, Joanna; Orzechowska, Barbara; Pabijan, Joanna; Seweryn, Sara; Lekka, Małgorzata
Graphical abstract: Highlights: Atomic force microscopy in force spectroscopy mode enables to quantify cell cancer characteristics. Single cell deformability can be used as a biomarker of cancer-related changes since cancerous cells differ significantly from normal ones. Quantification of ligand-receptor interaction can be useful in search of molecular targets for anti-cancer drugs. Abstract: From the first experiments of the atomic force microscopy (AFM) with biological samples, the range of its potential applications grows extensively. One of them is the use of AFM to characterize biophysical fingerprints of cancer progression in search of non-labelled biomarkers of the disease. The technique offers various functionalities, starting from surface imaging to detection of interaction forces, delivering quantitative parameters that can describe changes characteristic for various diseases, including cancer. In this review, the special emphasis was laid on these studies that compare the AFM-derived properties of reference and cancerous cells using all functionalities from cellular deformability measurements to quantification of the interaction forces at the single-molecule and single-cell levels. Despite the large effort and evidence of the microscope applicability to detect pathologically altered cells, there are still practical challenges remained to be solved before AFM can be implemented for routine cancer tracking and diagnosis. To-date, the AFM can be used to achieve a better understanding of cancer-related processes and mechanisms that could be further employed to design high-resolution clinical assays in a quantitative way.